Design of a novel three phase hybrid converter for microgrids application using renewable energy sources - Devulal, Bhukya; Siva, Manickam; Kumar, Dasari Ravi (International Journal of Electrical and Computer Engineering (IJECE), 2025)
A multi-level inverter (MLI) plays a vital role in recent days with an increasing trend of usage of microgrid and distributed generator. MLIs are popular in high voltage and high-power applications. MLIs operates with dominant switching frequency pulse width-modulation (PWM) techniques. These MLIs not only generate the output voltage with fewer Harmonic but also reduces the dV/dt stress on switches. The induction machine connected to these MLIs, adds greater advantages in real time applications. This paper presents a novel 13 and 21-level hybrid H-bridge inverter (HHBI) connected to induction drive by using a photovoltaic module for microgrid applications using maximum power point tracking (MPPT) through a PV array. Hybrid H-bridge inverters combine elements from different inverter topologies to optimize appearance in terms of efficiency, harmonics and system complexity. The main aim is to reduce harmonics using high level of inverter and by controlling motor characteristics. Here a novel PWM control method is used for making the exchanging sequences for the corresponding switches. From the MATLAB results presented, it can be noticed that with the proposed methodology the THD is reduced to 4.66 and number of switches to 39, which reduces the complexity of the system. It also minimized the switching losses and increases efficiency.